The effects of social and educational disadvantage on the roles and functions of school resource officers. Issue 3 (15th August 2016) - Lynch, Caitlin G.; Gainey, Randy R.; Chappell, Allison T.
Abstract : Purpose: With the expansion of school resource officer programs and the increased use of harsh disciplinary measures in schools, there is a growing concern that school safety measures are contributing to the school-to-prison pipeline, particularly in already disadvantaged schools. However, there is a lack of research on the relationship between social and educational disadvantage in schools and the roles and functions of school resource officers. The paper aims to discuss these issues. Design/methodology/approach: Using the School Survey on Crime and Safety (2006), this paper utilized structural equation modeling to investigate to what extent, if any, does social and educational disadvantage in schools influence the roles and functions of school resource officers. Findings: Findings suggest that school resource officers assigned to schools with greater levels of social and educational disadvantage perform more law enforcement-related functions, while school resource officers assigned to schools with less social and educational disadvantage perform more education-related functions. Originality/value: There is a lack of empirical literature on the specific roles and functions of school resource officers and whether or not the varying levels of social and educational disadvantage can predict how school resource officers are utilized. The current study aims to address this gap in the literature by examining how the social and educational disadvantage of schools predicts the roles and functions of school resource officers.